Attitude Toward Seeking Professional Psychological Help Among Community-Dwelling Population in China - Chen, Pan; Liu, Xiu Jun; Wang, Xiao Qin; Yang, Bing Xiang; Ruan, Juan; Liu, Zhongchun (Frontiers in Psychiatry, 2020)
Objective To explore the attitudes and factors in seeking professional psychological help among a Chinese community-dwelling population in order to promote positive help-seeking behaviors and better utilization of mental health services. Methods Using system and simple random sampling with Kish selection table methods, 912 community-dwelling residents were included in this study and asked about their attitudes toward seeking professional psychological help, depression symptoms, family function, depression literacy, help-seeking intention and stigma. Results Scores on the Attitudes Toward Seeking Professional Psychological Help scale (ATSPPH-SF) indicated a neutral attitude toward openness to seeking treatment for psychological problems and a negative attitude toward the value and need to seek treatment with a negative total score. Multiple linear regression analysis showed that gender, age, social support (employment status and family function), depression literacy, stigma and help-seeking intention are significantly associated with attitude toward seeking professional psychological help. Conclusion The overall attitude toward seeking professional psychological help is not optimistic, thus, more efforts are needed to enhance understanding. Effective interventions including mental health education, training of mental health professionals and popularizing the use of mental health services are essential, especially for the at-risk population.